The South African economy macroeconomic prospects for the medium term - Tarp, Finn 1951-; Brixen, Peter (Routledge studies in development economics, 1996)
Although the scenarios produced may seem specific to South Africa, the methodology outlined is just as applicable to the policy-making process elsewhere. The IMF's Financial Programming and the World Bank's Revised Minimum Standard Model were central to many macroeconomic management studies of the 1980s, which focused on stabilization and structural adjustment. This study shows for the first time how they can be quantitatively applied and illustrates their strengths and weaknesses